Adult islet1 Expression Outlines Ventralized Derivatives Along Zebrafish Neuraxis - Stephan W. Baeuml; Daniela Biechl; Mario F. Wullimann (Frontiers Media S.A., 2019)
Signals issued by dorsal roof and ventral floor plates, respectively, underlie the major patterning process of dorsalization and ventralization during vertebrate neural tube development. The ventrally produced morphogen Sonic hedgehog (SHH) is crucial for vertebrate hindbrain and spinal motor neuron development. One diagnostic gene for motor neurons is the LIM/homeodomain gene islet1, which has additional ventral expression domains extending into mid- and forebrain. In order to corroborate motor neuron development and, in particular, to improve on the identification of poorly documented zebrafish forebrain islet1 populations, we studied adult brains of transgenic islet1-GFP zebrafish (3 and 6 months). This molecular neuroanatomical analysis was supported by immunostaining these brains for tyrosine hydroxylase (TH) or choline acetyltransferase (ChAT), respectively, revealing zebrafish catecholaminergic and cholinergic neurons. The present analysis of ChAT and islet1-GFP label confirms ongoing adult expression of islet1 in zebrafish (basal plate) midbrain, hindbrain, and spinal motor neurons. In contrast, non-motor cholinergic systems lack islet1 expression. Additional presumed basal plate islet1 positive systems are described in detail, aided by TH staining which is particularly informative in the diencephalon. Finally, alar plate zebrafish forebrain systems with islet1 expression are described (i.e., thalamus, preoptic region, and subpallium). We conclude that adult zebrafish continue to express islet1 in the same brain systems as in the larva. Further, pending functional confirmation we hypothesize that the larval expression of sonic hedgehog (shh) might causally underlie much of adult islet1 expression because it explains findings beyond ventrally located systems, for example regarding shh expression in the zona limitans intrathalamica and correlated islet1-GFP expression in the thalamus.